Improving Understanding of Multiculturalism through Socialization of BIPA Learning at UMS for Students at SMA Muhammadiyah PK Kottabarat, Surakarta - Sulistyono, Yunus; Putri, Nadia Aprilia Kartikasari; Aprilyana, Niken (Universitas Muhammadiyah Surakarta, 2024)
The results of community service activities at SMA Muhammadiyah PK Kottabarat provide the aim of (1) deepening students' understanding of the existence and position of the Indonesian language and (2) deepening students' understanding of the Indonesian Language Teaching Program for Foreign Language Learners (BIPA). The existence of the Indonesian language as a state identity, as well as a means of diplomatic strategy, is able to advance the Indonesian language. The results of this community service showed that students participated in the activities very enthusiastically. The results of this brainstorming phase also show that students are increasingly aware of the importance of the strategic role of Indonesian and the Indonesian national language as a communication tool. It can also be seen from the feedback phase that students are increasingly aware of the cultural, racial and ethnic diversity that exists in the world.